Back to where they were: The socio-discursive representation of transgender sex workers and urban space in a television news report - Soich, Matías (2021)
Despite significant advances in recent years, Argentina’s transgender community still faces structural social exclusion. For a vast majority of transvestites and transgender women, early expulsion from the family home and the educational system results in having to resort to prostitution as their only option for surviving. Police edicts and other similar devices are used to penalize prostitution and persecute transgender people in public places, showing that prejudice and violence against their identities also manifest in the control of urban space. Here I present the results of an in-depth qualitative linguistic analysis of a 2018 television news report about the temporary relocation of the transgender sex workers from their usual location in the Bosques de Palermo, the biggest public park in the City of Buenos Aires. The theoretical frame is Critical Discourse Analysis and the methodology is inductive and qualitative. The analysis centers on the linguistic resources that define the socio-discursive representation about the transgender sex workers in relation with urban space and the city’s government. The bases of the analysis are the Synchronic-Diachronic Method for the Linguistic Analysis of Texts and the Method of Converging Linguistic Approaches. These methods revealed, in the first place, that the transvestites and transgender women are represented as mere occupants of public space through their close association with the discursive category of Space. In the second place, they are represented as fundamentally passive in relation to the Government of the City of Buenos Aires; while, at the same time, the government’s responsibility for their displacement is systematically mitigated. Finally, the lack of work alternatives to prostitution for the transgender community is naturalized through the persistent association of the discursive categories connected with transgender people, prostitution and urban space. If we compare these results with those of previous research, we can see that these discursive features—none of which challenge the status quo—remain one of the basic components of the socio-discursive representation of transgender people elaborated by the mainstream media.